A Small Actions to Big Impacts: Environmental Concern Messages In Gojek Youtube Ads #Dariaksikecil - Amelia Umi Pratiwi; Riski Apriliani (Jurnal Dakwah dan Komunikasi, 2026)
Purpose −  This study aims to analyze the representation of educational message in Gojek’s commercial ad on YouTube, Roland Barthes’s semiotic approach is used for the analysis. In addition to merely promoting services, in the context of digital ad, the state of understanding Gojek also contains embedded messages related to safety, health, and social issues. In relation to this,   Method – The study applies the qualitative method and content analysis technique to identify the visual, text, and audio elements of ads that carry an educational message in them. The ads documentation was carried out by collecting the Gojek commercials in its YouTube channel. The identification of educational messages was analyzed using Barthes’s concepts of denotation and connotation in order to derive the connotation incorporated in the signs   Findings −  The study reveals that in the commercials under study, Gojek sends educational messages through symbols that touch upon everyday life but convey a deeper message in the form of social responsibility and safety. The receivers of such state of understanding respond to the Gojek’s educational approach positively as it incites the demand for services and makes a positive impact on society. Therefore, it is concluded that Gojek successfully uses YouTube commercials to educate the target audience and enhance the popular image of the service